Provisions of economic concentrations between undertakings A comparative study - حسين اكرم محمد (Journal of Legal Sciences, 2006)
Economic concentration between undertakings is considered of common transactions in the commercial environment . So it was not seen as practices that can affect on the competition, or that it is misused to achieve purposes that are contrary to free and fair competition. In fact, concentration Transactions may to be affect on competition, Where Economic concentration has undeniable benefits, so it was not possible to prevent these Transactions. Instead, the laws tended to control concentration and avoid harming it. And obtain of its benefits. This study highlights on the provisions of economic concentration between undertakings, and detection of the mechanism through which to control it, and avoid the harmful effects of the market, through the study of a number of European and American laws and compared with Iraqi law.